Development of a Methodology and Evaluation of Pesticides Against Aceria litchii and Its Predator Phytoseius intermedius (Acari: Eriophyidae, Phytoseiidae) - Azevedo, L. H. [UNESP]; Moraes, G. J.; Yamamoto, P. T.; Zanardi, O. Z. (Entomological Soc Amer, 2013)
The litchi erineum mite, Aceria litchii (Keifer), is the major pest of litchi, Litchi chinensis Sonnerat (Sapindaceae). This study evaluated the effect of 11 pesticides on the survival of A. litchii as well as on the survival and reproduction of Phytoseius intermedius Evans& McFarlane, the predator most found in association with it in Brazil. The containment of A. litchii in small petri dishes whose bottoms were covered with a solidified paste made of a mixture of gypsum and activated charcoal (9: 1 in volume), kept humid, was shown to be adequate for this type of study. For the evaluation of the effect of pesticides on A. litchii, mites leaving the erinia from the pieces of litchi leaves (removed from the plants approximate to 24 h earlier) were sprayed under a Potter tower and immediately transferred to the 2.5-cm-diameter petri dishes. After 2, 12, 24, and 48 h of the application, the dishes were examined to evaluate the mite survival. The four pesticides causing the highest levels A. litchii mortality, as well as azadirachtin, were tested for the effect on P. intermedius. For this test, experimental units consisted of discs of uninfested litchi leaves also sprayed under a Potter tower before introducing the predators. Survival and oviposition of the predator were evaluated every 24 h for 5 consecutive days; viability of the eggs laid was also evaluated. Highest mortality of A. litchii occurred with the application of fenpyroximate, sulfur, abamectin, and hexythiazox. Azadirachtin was considered moderately harmful to the predator P. intermedius, whereas other pesticides were classified as harmful. Despite the low efficiency of azadirachtin in the control of the pest, its relative selectivity to P. intermedius would encourage the evaluation on field condition, especially for use in organic production systems.
Keywords: litchi; litchi erineum mite; predatory mite; Selectivity